2020
DOI: 10.1002/celc.202000307
|View full text |Cite
|
Sign up to set email alerts
|

Simple “Signal‐Off” Electrochemical Aptasensor Based on Aptamer‐Cu3(PO4)2 Hybrid Nanoflowers/Graphene Oxide for Carcinoembryonic Antigen Detection

Abstract: A signal-off aptasensor was described based on well-designed aptamer-Cu 3 (PO 4 ) 2 hybrid nanoflowers&graphene oxide composites (aptamer-Cu 3 (PO 4 ) 2 HNF&GO) as an effective sensing platform and molybdophosphate precipitation as the signaling element. The aptamer, as the biorecognition unit grafted on aptamer-Cu 3 (PO 4 ) 2 HNF&GO by the specificity of streptavidin and biotin, captured the carcinoembryonic antigen (CEA) through specific interaction. The molybdophosphate precipitation were formed by the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A variety of nanomaterials and nanocomposites was used both for the aptamer immobilisation and labelling: graphene-based nanomaterials [ 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 ], nanocomposite Zr metal–organic frameworks with Ag nanoclusters [ 257 ], and avidin-gated mesoporous silica nanoparticles [ 258 ].…”
Section: Electrochemical Assays For Cancer Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of nanomaterials and nanocomposites was used both for the aptamer immobilisation and labelling: graphene-based nanomaterials [ 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 ], nanocomposite Zr metal–organic frameworks with Ag nanoclusters [ 257 ], and avidin-gated mesoporous silica nanoparticles [ 258 ].…”
Section: Electrochemical Assays For Cancer Biomarkersmentioning
confidence: 99%
“…The Cu 3 (PO 4 ) 2 nanoflowers/GO nanocomposites (Cu 3 (PO 4 ) 2 NF@GO) represented another platform for the biotinylated DNA aptamer immobilisation, via the biotin—streptavidin linkage [ 255 ]. The reaction of molybdophosphate precipitation from Cu 3 (PO 4 ) 2 NF@GO and molybdate (MoO 4 2− ) electrochemistry were used as an indicator.…”
Section: Electrochemical Assays For Cancer Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] Referring to the existing studies of VEGF 165 and CEA aptamers, the aptamer sequences designed in this study are shown in Table 1. [39][40][41][42] The VEGF 165 and CEA aptamers have been proved to bind to their corresponding targets with high affinity, respectively. And the great dissociation constant (Kd) values of the VEGF 165 and CEA aptamers were indeed already demonstrated, with a Kd value of 37.9 nM for VEGF 165 and 5 nM for CEA.…”
Section: Introductionmentioning
confidence: 99%